Exposure in Transit: In Vivo Exposure Therapy Treatment for Agoraphobia Symptoms in Teenage Girls - Comes, Brynn (Advances in Social Sciences Research Journal, 2025)
Agoraphobia is an anxiety disorder that is typically characterized by avoiding public spaces, including crowds and public transportation to the extent that it impacts one’s quality of life. There are a few methods of cognitive behavioral therapy (CBT) that have been proven as effective against agoraphobia, but recently people have been using in vivo exposure therapy more because of its higher efficacy. Because of this, this research focuses on a method of in vivo exposure therapy for the agoraphobic symptom of having a fear of public transportation, this method being that the participants would go on an underground subway system in order to see if their agoraphobic symptoms, measured on a scale from 0-100, would decrease within the span of 3 weeks. After the study concluded the numbers did decrease for all participants, making the use of the subway a viable way of reducing agoraphobic symptoms for the study group of teenage girls. Future studies are advised to test out this method on other study groups.